Unveiling the Dynamics of Expectation, Flow, Enjoyment, and Satisfaction: Drivers of Continued Subscription Intentions Among Netflix Users - Masao, Muhammad; Salehudin, Imam (The South East Asian Journal of Management, 2023)
Research Aims: This study investigates the determinants impacting the intention of Netflix users to continue using the platform. By leveraging the extended Expectation-Confirmation Model of continued IT usage and hedonic variables, including Confirmation, Flow, Perceived Usefulness, Perceived Enjoyment, and Satisfaction, the research aims to discern the most influential factors. Design/Methodology/Approach: The research recruited 271 participants through non-probabilistic purposive sampling, targeting Indonesian Netflix subscribers active within the preceding six months who were at least 17 years old at the time of the study. Covariance-based Structural Equation Modelling was employed to analyse the collected data. Research Findings: User enjoyment and Satisfaction mediate the relationships between Flow and Confirmation with Netflix's continuance intention. Flow emerges as the preeminent determinant of continuance intention among the exogenous variables. While Flow's influence on continuance intention is mediated by Satisfaction and Enjoyment, there is no direct effect between Flow and Satisfaction. Perceived Usefulness exhibits no substantial correlation with continuance intention. Theoretical Contribution/Originality: This research underscores the pivotal role of Flow in driving enjoyment and continuance intention within video subscription services like Netflix. Managerial Implications in the South East Asian Context: The study offers insights into the preferences and behaviours of Netflix users in the Southeast Asian context, employing Indonesia as a focal point. This valuable information equips Netflix and other regional SVOD providers to strategically enhance their offerings and services. Research Limitations & Implications: To enhance the robustness of the findings, future research should encompass broader and more diverse populations for comparative purposes. Including new variables, such as digital piracy and perceived ease of use, would contribute to a comprehensive understanding of the dynamics at play.